Examples with solutions for Powers of a Fraction: Inverse formula

Exercise #1

Insert the corresponding expression:

3686= \frac{3^6}{8^6}=

Video Solution

Step-by-Step Solution

To solve this problem, we will apply the rule of exponentiation for fractions. This rule states that anbn=(ab)n\frac{a^n}{b^n} = \left(\frac{a}{b}\right)^n, where aa and bb are non-zero numbers and nn is an integer.

Let's go through the solution step-by-step:

  • Step 1: Recognize that the expression we need to rewrite is 3686\frac{3^6}{8^6}.
  • Step 2: Apply the power of a fraction rule. According to this rule, 3686=(38)6\frac{3^6}{8^6} = \left(\frac{3}{8}\right)^6.
  • Step 3: Thus, the expression 3686\frac{3^6}{8^6} simplifies to (38)6\left(\frac{3}{8}\right)^6.

The solution to the problem is that the expression can be rewritten as (38)6 \left(\frac{3}{8}\right)^6 .

Answer

(38)6 \left(\frac{3}{8}\right)^6

Exercise #2

Insert the corresponding expression:

29119= \frac{2^9}{11^9}=

Video Solution

Step-by-Step Solution

To solve this problem, we'll employ the exponent rules for fractions:

  • Step 1: Recognize that 29119\frac{2^9}{11^9} follows the general form anbn\frac{a^n}{b^n}.
  • Step 2: Apply the property (ab)n=anbn\left(\frac{a}{b}\right)^n = \frac{a^n}{b^n}.
  • Step 3: Substitute into the property to express the fraction as (211)9\left(\frac{2}{11}\right)^9.

Let's work through the steps in detail:

Step 1: The expression 29119\frac{2^9}{11^9} can be viewed as each number, 2 and 11, raised to the 9th power in a fraction.

Step 2: Utilize the exponent rule (ab)n=anbn\left(\frac{a}{b}\right)^n = \frac{a^n}{b^n} to rewrite the fraction with a single power.

Step 3: Therefore, the expression 29119\frac{2^9}{11^9} simplifies to (211)9\left(\frac{2}{11}\right)^9.

Therefore, the correct answer is indeed (211)9\left(\frac{2}{11}\right)^9.

The correct choice from the provided options is:

(211)9 \left(\frac{2}{11}\right)^9

Answer

(211)9 \left(\frac{2}{11}\right)^9

Exercise #3

Insert the corresponding expression:

1797= \frac{1^7}{9^7}=

Video Solution

Step-by-Step Solution

To solve this problem, we'll apply the formula for the power of a quotient:

  • Step 1: Identify the expression 1797 \frac{1^7}{9^7} .
  • Step 2: Recognize that anbn=(ab)n \frac{a^n}{b^n} = \left( \frac{a}{b} \right)^n applies here. The numerator is a7=17 a^7 = 1^7 , and the denominator is b7=97 b^7 = 9^7 .
  • Step 3: Apply the formula: 1797=(19)7 \frac{1^7}{9^7} = \left( \frac{1}{9} \right)^7 .

In step 2, we used the property that allows us to rewrite 1797 \frac{1^7}{9^7} as (19)7 \left( \frac{1}{9} \right)^7 , which is more convenient for interpretation or further calculations.

Therefore, the expression 1797 \frac{1^7}{9^7} can be rewritten as (19)7 \left( \frac{1}{9} \right)^7 .

Answer

(19)7 \left(\frac{1}{9}\right)^7

Exercise #4

Insert the corresponding expression:

2474= \frac{2^4}{7^4}=

Video Solution

Step-by-Step Solution

To solve this problem, we will apply the exponent rule for powers of a fraction.

  • Step 1: Understand the given expression 2474\frac{2^4}{7^4}.
  • Step 2: Use the formula anbn=(ab)n\frac{a^n}{b^n} = \left(\frac{a}{b}\right)^n to rewrite the expression.
  • Step 3: Apply this rule to rewrite 2474=(27)4\frac{2^4}{7^4} = \left(\frac{2}{7}\right)^4.

This shows that instead of writing separate powers for the numerator and denominator, we can express it as a single fraction raised to that power.

Thus, the expression 2474\frac{2^4}{7^4} corresponds to (27)4\left(\frac{2}{7}\right)^4.

The correct choice from the given options is:

  • Choice 3: (27)4 \left(\frac{2}{7}\right)^4

Therefore, the solution to the problem is (27)4 \left(\frac{2}{7}\right)^4 .

Answer

(27)4 \left(\frac{2}{7}\right)^4

Exercise #5

Insert the corresponding expression:

1232= \frac{1^2}{3^2}=

Video Solution

Step-by-Step Solution

To solve this problem, let's follow these steps:

  • Step 1: Identify the given expression. We have 1232 \frac{1^2}{3^2} .
  • Step 2: Apply the appropriate rule for powers of fractions: ambm=(ab)m \frac{a^m}{b^m} = \left(\frac{a}{b}\right)^m .
  • Step 3: Simplify the expression using this rule.

Now, let's proceed through each step in detail:

Step 1: We start with the given expression 1232 \frac{1^2}{3^2} .

Step 2: According to the rule for powers of fractions, we write this expression as:
1232=(13)2 \frac{1^2}{3^2} = \left(\frac{1}{3}\right)^2 .

Step 3: This simplification converts both the numerator and the denominator's power into a single power of the fraction (13) \left(\frac{1}{3}\right) .

Therefore, the expression 1232 \frac{1^2}{3^2} is equivalent to (13)2 \left(\frac{1}{3}\right)^2 .

Comparing with the given answer choices, the correct choice is \( \text{Choice 2: } (13)2 \left(\frac{1}{3}\right)^2 .

Answer

(13)2 \left(\frac{1}{3}\right)^2

Exercise #6

Insert the corresponding expression:

710910= \frac{7^{10}}{9^{10}}=

Video Solution

Step-by-Step Solution

To solve this problem, let's transform the expression 710910\frac{7^{10}}{9^{10}}.

  • Step 1: Identify the Form

The expression 710910\frac{7^{10}}{9^{10}} fits the pattern ambm\frac{a^m}{b^m}.

  • Step 2: Apply the Power of a Quotient Rule

The power of a quotient formula is ambm=(ab)m\frac{a^m}{b^m} = \left(\frac{a}{b}\right)^m.

Substitute a=7a = 7, b=9b = 9, and m=10m = 10 into this formula, and we have:

710910=(79)10\frac{7^{10}}{9^{10}} = \left(\frac{7}{9}\right)^{10}.

We can see that this transformation results in the expression (79)10\left(\frac{7}{9}\right)^{10}, which matches answer choice 1.

Therefore, the final expression is (79)10\left(\frac{7}{9}\right)^{10}.

Thus, the correct reformulated expression is (79)10\left(\frac{7}{9}\right)^{10}.

Answer

(79)10 \left(\frac{7}{9}\right)^{10}

Exercise #7

Insert the corresponding expression:

204314= \frac{20^4}{31^4}=

Video Solution

Step-by-Step Solution

To solve this problem, we need to rewrite the given expression 204314 \frac{20^4}{31^4} using properties of exponents.

Let's take these steps:

  • Step 1: Recognize the expression as a fraction raised to a power. The problem provides 204314 \frac{20^4}{31^4} .
  • Step 2: Apply the power of a fraction rule: For any real numbers a a and b b , and a positive integer n n , (ab)n=anbn\left( \frac{a}{b} \right)^n = \frac{a^n}{b^n} .

Applying Step 2, we write:

204314=(2031)4\frac{20^4}{31^4} = \left(\frac{20}{31}\right)^4.

Thus, the corresponding expression is (2031)4 \left(\frac{20}{31}\right)^4 .

Therefore, the solution to the problem is (2031)4\left(\frac{20}{31}\right)^4.

Answer

(2031)4 \left(\frac{20}{31}\right)^4

Exercise #8

Insert the corresponding expression:

123233= \frac{12^3}{23^3}=

Video Solution

Step-by-Step Solution

To solve this problem, we recognize the application of exponent rules for powers of fractions. The expression 123233\frac{12^3}{23^3} can be rewritten by using the formula ambm=(ab)m\frac{a^m}{b^m} = \left(\frac{a}{b}\right)^m.

Let's apply this to the given problem:

  • Step 1: Identify the structure as ambm\frac{a^m}{b^m}, where a=12a = 12, b=23b = 23, and m=3m = 3.
  • Step 2: Use the formula ambm=(ab)m\frac{a^m}{b^m} = \left(\frac{a}{b}\right)^m to transform 123233\frac{12^3}{23^3} into (1223)3\left(\frac{12}{23}\right)^3.

The expression 123233\frac{12^3}{23^3} simplifies to (1223)3\left(\frac{12}{23}\right)^3.

Therefore, the correct corresponding expression is (1223)3\left(\frac{12}{23}\right)^3.

Answer

(1223)3 \left(\frac{12}{23}\right)^3

Exercise #9

Insert the corresponding expression:

1565= \frac{1^5}{6^5}=

Video Solution

Step-by-Step Solution

To solve this problem, we need to express 1565 \frac{1^5}{6^5} using the power of a fraction rule:

  • Step 1: Identify that both the numerator and denominator are raised to the same power, 5.
  • Step 2: Recognize that the expression can be rewritten as (16)5 \left(\frac{1}{6}\right)^5 using the power of a fraction rule: (ab)n=anbn\left(\frac{a}{b}\right)^n = \frac{a^n}{b^n}.

Applying the formula, we convert 1565 \frac{1^5}{6^5} into (16)5 \left(\frac{1}{6}\right)^5 .

Therefore, the solution to the problem and correct multiple-choice answer is (16)5 \left(\frac{1}{6}\right)^5 , which corresponds to choice 2.

Answer

(16)5 \left(\frac{1}{6}\right)^5

Exercise #10

Insert the corresponding expression:

105175= \frac{10^5}{17^5}=

Video Solution

Step-by-Step Solution

To solve the given problem, we want to rewrite the expression 105175 \frac{10^5}{17^5} using the rules of exponents.

  • Step 1: Recognize that both the numerator and the denominator are raised to the 5th power.
  • Step 2: Apply the rule (ab)n=anbn\left(\frac{a}{b}\right)^n = \frac{a^n}{b^n}, which allows us to combine the power into a single expression.

By applying this rule, we have:

105175=(1017)5 \frac{10^5}{17^5} = \left(\frac{10}{17}\right)^5

This shows that the original expression can be rewritten as a single power of a fraction.

Therefore, the simplified form of the expression is (1017)5\left(\frac{10}{17}\right)^5.

Answer

(1017)5 \left(\frac{10}{17}\right)^5

Exercise #11

Insert the corresponding expression:

167= \frac{1}{6^7}=

Video Solution

Step-by-Step Solution

To solve this problem, we will rewrite the expression 167\frac{1}{6^7} using the rules of exponents:

Step 1: Identify the given fraction.

We start with 167\frac{1}{6^7}, where the base in the denominator is 6, and the exponent is 7.

Step 2: Apply the formula for negative exponents.

The formula an=1ana^{-n} = \frac{1}{a^n} allows us to rewrite a reciprocal power as a negative exponent. This means the expression 167\frac{1}{6^7} can be rewritten as 676^{-7}.

Step 3: Conclude with the answer.

By transforming 167\frac{1}{6^7} to its equivalent form using negative exponents, the expression becomes 676^{-7}.

Therefore, the correct expression is 67\boxed{6^{-7}}, which corresponds to choice 2 in the given options.

Answer

67 6^{-7}

Exercise #12

Insert the corresponding expression:

132= \frac{1}{3^2}=

Video Solution

Step-by-Step Solution

To solve this problem, we'll use the rule of negative exponents:

  • Step 1: Identify that the given expression is 132\frac{1}{3^2}.
  • Step 2: Recognize that 132\frac{1}{3^2} can be rewritten using the negative exponent rule.
  • Step 3: Apply the formula 1an=an\frac{1}{a^n} = a^{-n} to the expression 132\frac{1}{3^2}.

Now, let's work through these steps:

Step 1: We have 132\frac{1}{3^2} where 3 is the base and 2 is the exponent.

Step 2: Using the formula, convert the denominator 323^2 to 323^{-2}.

Step 3: Thus, 132=32\frac{1}{3^2} = 3^{-2}.

Therefore, the solution to the problem is 323^{-2}.

Answer

32 3^{-2}

Exercise #13

Insert the corresponding expression:

152= \frac{1}{5^2}=

Video Solution

Step-by-Step Solution

To solve the given problem, we need to express 152 \frac{1}{5^2} using negative exponents. We'll apply the formula for negative exponents, which is 1an=an \frac{1}{a^n} = a^{-n} :

  • Identify the base and power in the denominator. Here, the base is 5 5 and the power is 2 2 .
  • Apply the inverse formula: 152=52 \frac{1}{5^2} = 5^{-2} .

Thus, the equivalent expression for 152 \frac{1}{5^2} using a negative exponent is 52 5^{-2} .

Answer

52 5^{-2}

Exercise #14

Insert the corresponding expression:

142= \frac{1}{4^2}=

Video Solution

Step-by-Step Solution

To solve the problem of expressing 142\frac{1}{4^2} using powers with negative exponents:

  • Identify the base in the denominator: 4 raised to the power 2.
  • Apply the rule for negative exponents that states 1an=an\frac{1}{a^n} = a^{-n}.
  • Express 142\frac{1}{4^2} as 424^{-2}.

Thus, the expression 142\frac{1}{4^2} can be rewritten as 42 4^{-2} .

Answer

42 4^{-2}

Exercise #15

Insert the corresponding expression:

1202= \frac{1}{20^2}=

Video Solution

Step-by-Step Solution

To solve this problem, we will use the properties of exponents. Specifically, we will convert the expression 1202 \frac{1}{20^2} into a form that uses a negative exponent. The general relationship is that 1an=an \frac{1}{a^n} = a^{-n} .

Applying this rule to the given expression:

  • Step 1: Identify the current form, which is 1202 \frac{1}{20^2} .
  • Step 2: Apply the negative exponent rule: 1202=202 \frac{1}{20^2} = 20^{-2} .
  • Step 3: This expression, 202 20^{-2} , represents 1202 \frac{1}{20^2} using a negative exponent.

Therefore, the expression 1202 \frac{1}{20^2} can be expressed as 202 20^{-2} , which aligns with choice 1.

Answer

202 20^{-2}

Exercise #16

Insert the corresponding expression:

57×47197= \frac{5^7\times4^7}{19^7}=

Video Solution

Step-by-Step Solution

To solve this problem, we need to simplify the expression 57×47197 \frac{5^7 \times 4^7}{19^7} .

We start by applying the property of exponents which states that for any numbers a a , bb, and c c , ac×bc=(a×b)c a^c \times b^c = (a \times b)^c . In this case, we have:

57×47=(5×4)7 5^7 \times 4^7 = (5 \times 4)^7

Thus, the original expression becomes:

(5×4)7197 \frac{(5 \times 4)^7}{19^7}

Now, using the exponent rule for powers of a fraction, (ab)c=acbc\left(\frac{a}{b}\right)^c = \frac{a^c}{b^c}, this further simplifies as:

(5×419)7 \left(\frac{5 \times 4}{19}\right)^7

Therefore, when we look at the answer choices, both options:

  • (5×4)7197 \frac{(5 \times 4)^7}{19^7}
  • (5×419)7 \left(\frac{5 \times 4}{19}\right)^7

are equivalent to our simplified expression. This corresponds to choice B and choice C in the given question. Therefore, both B and C are correct.

To conclude, the correct answer is B+C are correct \text{B+C are correct} .

Answer

B+C are correct

Exercise #17

Insert the corresponding expression:

65135×45= \frac{6^5}{13^5\times4^5}=

Video Solution

Step-by-Step Solution

To solve this problem, we aim to rewrite the given expression using the properties of exponents. The expression we need to deal with is 65135×45 \frac{6^5}{13^5 \times 4^5} .

We can simplify this using the formula for powers of fractions, which states that if two exponents are the same, we can treat the fraction as a whole raised to that exponent: ambm=(ab)m \frac{a^m}{b^m} = \left(\frac{a}{b}\right)^m .

Applying this to the problem, considering the expression 65(13×4)5 \frac{6^5}{(13 \times 4)^5} all raised to the power of 5 can be rewritten, using our formula, as a single fraction raised to the same power:
(613×4)5 \left(\frac{6}{13 \times 4}\right)^5 .

This simplifies the entire expression to a clear fraction raised to the power 5. Therefore, the corresponding expression to the original problem is:

(613×4)5 \left(\frac{6}{13 \times 4}\right)^5 .

Answer

(613×4)5 \left(\frac{6}{13\times4}\right)^5

Exercise #18

Insert the corresponding expression:

4353×73= \frac{4^3}{5^3\times7^3}=

Video Solution

Step-by-Step Solution

To solve this problem, we will apply the rule for powers of a quotient. By recognizing that the expression 4353×73 \frac{4^3}{5^3 \times 7^3} can be seen in terms of powers, we can reformulate it:

4353×73=43(5×7)3 \frac{4^3}{5^3 \times 7^3} = \frac{4^3}{(5 \times 7)^3}

Now, we see this as a single fraction raised to the same power, which can be expressed using the power of a fraction rule:

43(5×7)3=(45×7)3 \frac{4^3}{(5 \times 7)^3} = \left(\frac{4}{5 \times 7}\right)^3

Thus, the expression given is equivalent to

(45×7)3 \left(\frac{4}{5 \times 7}\right)^3 .

Answer

(45×7)3 \left(\frac{4}{5\times7}\right)^3

Exercise #19

Insert the corresponding expression:

66×11656×136= \frac{6^6\times11^6}{5^6\times13^6}=

Video Solution

Step-by-Step Solution

To solve this problem, we'll follow these steps:

  • Step 1: Apply the product of powers formula

  • Step 2: Simplify the combined powers into a single fraction with one exponent

Now, let's work through each step:
Step 1: Using (am×bm)=(a×b)m(a^m \times b^m) = (a \times b)^m, we get:
(66×116)=(6×11)6(6^6 \times 11^6) = (6 \times 11)^6 and (56×136)=(5×13)6(5^6 \times 13^6) = (5 \times 13)^6.

Step 2: Simplifying the expression, we get:
(66×116)(56×136)=(6×11)6(5×13)6=(6×115×13)6\frac{(6^6 \times 11^6)}{(5^6 \times 13^6)} = \frac{(6 \times 11)^6}{(5 \times 13)^6} = \left(\frac{6 \times 11}{5 \times 13}\right)^6.

This transformation matches both option B and C in the provided answer choices.

Therefore, the correct answer isB + C are correct \textbf{B + C are correct} .

Answer

B+C are correct

Exercise #20

Insert the corresponding expression:

510×810410×710= \frac{5^{10}\times8^{10}}{4^{10}\times7^{10}}=

Video Solution

Step-by-Step Solution

To simplify the expression 510×810410×710 \frac{5^{10}\times8^{10}}{4^{10}\times7^{10}} , we start by applying the property of exponents: (a×b)n=an×bn (a \times b)^n = a^n \times b^n .

Step 1: Rewrite the expression. Notice that both the numerator and the denominator consist of two numbers, each raised to the power of 10.

510×810410×710=(5×8)10(4×7)10 \frac{5^{10} \times 8^{10}}{4^{10} \times 7^{10}} = \frac{(5 \times 8)^{10}}{(4 \times 7)^{10}}

Now, we notice we can apply the equality for exponential simplification:

(5×84×7)10=(5×8)10(4×7)10 \left(\frac{5 \times 8}{4 \times 7}\right)^{10} = \frac{(5 \times 8)^{10}}{(4 \times 7)^{10}}

Concluding, the simplified expression of the given problem is equivalent to option "1":

The expression simplifies to (5×8)10(4×7)10\frac{\left(5\times8\right)^{10}}{\left(4\times7\right)^{10}} , which aligns perfectly with choice id="1".

Therefore, the final answer is:

(5×8)10(4×7)10 \frac{\left(5\times8\right)^{10}}{\left(4\times7\right)^{10}} .

Answer

(5×8)10(4×7)10 \frac{\left(5\times8\right)^{10}}{\left(4\times7\right)^{10}}